Social protection in an aspiring 'developmental state': The political drivers of Ethiopia's PSNP - Tom Lavers (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Ethiopia's Productive Safety Net Programme is among the largest social protection programmes in Africa and has been promoted as a model for the continent. This paper analyses the political drivers of the programme, arguing that elite commitment can be understood in the context of shifts within Ethiopia's political settlement and the government's evolving development strategy. Foreign donors provided policy ideas and pushed for reform, but it was not until incentives flowing from the political settlement were favourable that elite commitment was secured. Even then, long-standing ideological commitments shaped the productive focus of the programme, ensuring consistency with the development strategy.
Keywords: H55; I38; O55; P48; 330; Ethiopia; food security; political settlements; process tracing; public works; social protection